Rapid Accumulation of Soil Carbon and Nitrogen in a Prairie Restoration Chronosequence. Issue 6 (20th September 2013) - Hernández, Daniel L.; Esch, Ellen H.; Alster, Charlotte J.; McKone, Mark J.; Camill, Phillip
Abstract : Understanding patterns of soil C and N accumulation in restored prairies is necessary to determine the sequestration potential of these systems. Estimates of C and N accumulation following prairie restoration are generally based on chronosequence studies. However, few studies have compared a chronosequence approach to direct measures of accumulation over time. Restored prairies in the Cowling Arboretum of Carleton College, Northfield, MN, were established annually from 1995 to 2007. In 2000 and 2010–2011, prairies were sampled for soil %C and %N and soil bulk density, allowing for a comparison of the effects of prairie age using a chronosequence approach to direct measures of C and N accumulation rates. Soil C and N content increased in all restorations, although there was no effect of field age across the chronosequence on C or N pools. However, rates of soil C and N accumulation decreased with restoration age, suggesting a rapid increase in the years immediately following agricultural conversion. This rapid accumulation was likely due to the turnover of annual and biennial species that dominated plant cover in the early in succession. This suggestion was supported by an observed increase in δ 13 C values with increasing prairie age. Thus, contributions from early successional species may result in rapid recovery of soil pools following restoration from agriculture. Direct measures of soil C and N accumulation may be necessary when initial variability among sites limit the ability of a chronosequence approach to detect significant changes in soil C and N content over short time periods.